The Effect of Personality Traits on COVID-19 Stress Level During the COVID-19 Pandemic in Turkey - BAYRI BİNGÖL, FADİME (My University, 2023)
Objective: This study aimed to examine the relationship between personality traits and Coronavirus disease-2019 (COVID-19) stress level. Methods: This descriptive correlational study was conducted between December 2020-January 2021 using an online survey of 360 participants. Data were collected using information form, COVID-19 stress scale, and the International Personality Item Pool-Big-Five inventory. Results: The participants had a mean age of 28.43±6.88 years and their mean years of education was 15.0±2.24 years. The mean total score on the COVID-19 stress scale was 53.87±10.78 (17-73), indicating moderate stress. Evaluation of the relationship between personality traits and COVID-19 stress revealed a positive correlation between scores on the extroversion subscale of the personality inventory and the compulsive checking subscale of the COVID-19 stress scale. Agreeableness and conscientiousness scores were also positively correlated with the compulsive checking and danger/contamination subscales of the COVID-19 stress scale. Conclusion: This study identified relationships between scores on the COVID-19 stress scale and the IPIP Big-Five factor markers. As high stress level is a risk factor for the development of psychiatric disorders, the early identification of stressed individuals is important improve public mental health. Keywords: COVID-19, stress, personality traits
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); COVID-19; stress; personality traits